The Filipino press and media, democracy, and development the book on the press and media - De Jesus, Melinda Q. (Diliman Quezon City, Philippines : University of the Philippines Press, 2001)
Another gem in the Pamana collection, this book reflects the role of media and the press in shaping sociopolitical development, and how certain events and circumstances helped shape their role. It is an attempt to help readers understand the past and how it may possibly affect the future of media and the press.
Part I. Media and Society -- Part II. Media in Philippine history -- Part III. Media and National Issues
Includes bibliographical references and index.
Keywords: FREEDOM OF THE PRESS PHILIPPINES